Прилад-автомат для дослідження полів інфрачервоної опроміненості в системі "опромінювач-об'єкт" - Щур, Ігор (Видавництво Національного університету «Львівська політехніка», 2002)
The automatic device with microprocessor operating system which scans in step regime the irradiation field by the IR irradiator was elaborated. The results of measurement of irradiation in its different intervals, taken during this process, are integrated and graphically recorded by two-dimensional self-registrating device, which allows to form the universal characteristics of energetic and quality of irradiation.